Tinjauan Penerapan Pengendalian Intern Melalui Sistem Informasi Akuntasi Terhadap Kegiatan Opersional Anjungan Tunai Mandiri - Roestiono, Harry; Munawar, Aang; Rostika, Siti (Jurnal Ilmiah Akuntansi Kesatuan, 2015)
The purpose of this study was to determine how the internal control in the operations of automated teller machines and how account information systems in the operation of automated teller machines are carried out by the bank. The research conducted over the operations leading to automatic teller machines that take place at the ATM machine located in the location of research. From these results conclude that intern control and accounting information systems run by BJB bank branch in the operational activities cash is going well. This can be seen from the operation of intem components and elements of the system are implemented in accordance with standard operational procedures set by the bank BJB Bogor Branch. Starting from the transaction, ATM cash hospitalization until the completion of the cash transaction error has been running well in accordance with the provisions of the bank Keywords : Internal Control, Accounting Information Systems, Automated Teller Machines Operations